(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: The purpose of this study was to see the improvement of teachers’ skills in compiling creative critical-based learning outcomes test instruments through collaborative participatory guidance for teachers of SMP Negeri 1 Brand in the 2018/2019 academic year and to see the increase in teacher activity in compiling creative critical-based learning outcomes test instruments. through collaborative participatory guidance for SMP Negeri 1 Brand teachers for the 2018/2019 school year. This study uses a school action research approach (action research) using a cyclical strategy. The research was conducted at SMP Negeri 1 Merek from August to November 2018. The subjects of this study were 39 class teachers of SMP Negeri 1 Brand. This research was conducted through collaborative participatory guidance by the researcher as the principal. The data collection technique was carried out using a rubric for assessing the ability of teachers to compose learning outcomes test instruments and rubrics for assessing teacher activities. Based on the research conducted, it can be concluded that; 1) there was an increase in teacher skills in compiling critical and creative-based learning outcomes test instruments from Cycle I to Cycle II with the material aspects of the questions increasing from an average of 2.4 to 3.2 in the good category, construction aspects increasing from an average of 1 .9 to 3.0 in the good category, and the language aspect rose from an average of 2.8 to 3.5 in the good category; 2) there was an increase in teacher activity in the preparation of creative critical-based learning outcomes test instruments from Cycle I to Cycle II with 8 aspects in Cycle I in the sufficient category and 2 aspects in the less category being all aspects in the good category in Cycle II. Keywords: Collaborative Participatory Guidance, Learning Outcome Test Instruments Abstrak: Tujuan penelitian ini adalah untuk melihat peningkatan keterampilan guru menyusun intrumen tes hasil belajar berbasis kritis kreatif melalui bimbingan partisipatif kolaboratif terhadap guru-guru SMP Negeri 1 Merek tahun pelajaran 2018/2019 dan melihat peningkatan aktivitas guru dalam menyusun intrumen tes hasil belajar berbasis kritis kreatif melalui bimbingan partisipatif kolaboratif terhadap guru-guru SMP Negeri 1 Merek tahun pelajaran 2018/2019. Penelitian ini menggunakan pendekatan penelitian tindakan sekolah (action research) dengan menggunakan strategi siklus. Penelitian dilaksanakan di SMP Negeri 1 Merek mulai Agustus sampai dengan Nopember 2018. Subyek penelitian ini adalah 39 guru kelas SMP Negeri 1 Merek. Penelitian ini dilaksanakan melalui bimbingan partisipatif kolaboratif oleh peneliti sebagai kepala sekolah. Teknik pengumpulan data dilakukan dengan rubrik penilaian kemampuan guru menyusun instrumen tes hasil belajar dan rubrik penilaian aktivitas guru. Berdasarkan penelitian yang dilakukan, dapat disimpulkan bahwa; 1) terjadi peningkatan keterampilan guru dalam menyusun instrumen tes hasil belajar berbasis kritis dan kreatif dari Siklus I ke Siklus II dengan aspek materi soal naik dari rata-rata 2,4 menjadi 3,2 dalam kategori baik, aspek konsruksi naik dari rata-rata 1,9 menjadi 3,0 dalam kategori baik, dan aspek bahasa naik dari rata-rata 2,8 menjadi 3,5 dalam kategori baik; 2) terjadi peningkatan aktivitas guru dalam penyusunan instrumen tes hasil belajar berbasis kritis kreatif dari Siklus I ke Siklus II dengan 8 aspek pada Siklus I dalam kategori cukup dan 2 aspek dalam kategori kurang menjadi seluruh aspek dalam kategori baik pada Siklus II. Kata Kunci : Bimbingan Partisipatif Kolaboratif, Instrumen Tes Hasil Belajar